2012
DOI: 10.2174/1876525401204010027
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of Osteoblasts and Citrate Production in Bone Formation: “Osteoblast Citration” as a New Concept for an Old Relationship

Abstract: It has been known for about seventy years that bone, in all vertebrates, contains uniquely high citrate levels. However, the role of citrate, its source, its regulation, and its implication in normal bone formation and in bone disorders have remained largely unknown. For the past thirty-five years, the relationship of citrate in bone has been a neglected area of attention and research. It has recently been discovered that citrate is critical for the structure of the apatite nanocrystal, and is required to impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 43 publications
6
91
0
Order By: Relevance
“…Although its function in bone formation remains largely unknown, recent research has discovered that citrate plays a large role in bone's unique stability, strength, and resistance to fracture by regulating apatite nanocrystal growth (8486). These recent findings have created a renewed interest in the role of citrate in bone physiology and development and provided a new hypothesis that osteoblasts are specialized citrate-producing cells that provide the necessary levels of citrate for proper bone formation (85, 87). A recent study has shown that citrate, whether presented on a biomaterial surface or supplemented into cell culture media, has unique effects on gene expression: It upregulates osterix, alkaline phosphatase, and osteopontin and downregulates osteocalcin in C2C12 myoblasts and human mesenchymal stem cells (88).…”
Section: Applications In Regenerative Engineeringmentioning
confidence: 99%
“…Although its function in bone formation remains largely unknown, recent research has discovered that citrate plays a large role in bone's unique stability, strength, and resistance to fracture by regulating apatite nanocrystal growth (8486). These recent findings have created a renewed interest in the role of citrate in bone physiology and development and provided a new hypothesis that osteoblasts are specialized citrate-producing cells that provide the necessary levels of citrate for proper bone formation (85, 87). A recent study has shown that citrate, whether presented on a biomaterial surface or supplemented into cell culture media, has unique effects on gene expression: It upregulates osterix, alkaline phosphatase, and osteopontin and downregulates osteocalcin in C2C12 myoblasts and human mesenchymal stem cells (88).…”
Section: Applications In Regenerative Engineeringmentioning
confidence: 99%
“…28 Costello et al discussed the speculated roles of citrate metabolism and production for the osteogenic differentiation of stem cells and bone formation. 29, 30 These latest findings are strong evidence that citrate should be involved in bone substitute design and has led to the development of a series of citrate-based composites for bone applications including poly (diol citrates)-HA (POC-HA), poly (ethylene glycol) maleate citrate-HA (PEGMC-HA), and citrate-based polymer blends-HA (CBPB-HA). 3136 …”
Section: Introductionmentioning
confidence: 99%
“…It is possible that aerobic glycolysis is necessary to fulfill the specific metabolic needs of osteoblasts. For instance, osteoblasts have been long known to produce and secrete a large amount of citrate 25,26 . Citrate in bone was recently shown to be critical for the structure of the apatite nanocrystal, providing stability, strength, and resistance to fracture 2729 .…”
Section: Aerobic Glycolysis In Osteoblastsmentioning
confidence: 99%